Hydrothermal liquefaction of Nannochloropsis oceanica in different solvents. (August 2016) - Caporgno, M.P.; Pruvost, J.; Legrand, J.; Lepine, O.; Tazerout, M.; Bengoa, C.
Graphical abstract: Highlights: High bio-oil yields were obtained from wet N. oceanica at low temperature. High temperatures increase bio-oil yields but decrease their quality. Alcohols as co-solvents increase the bio-oil yield from wet biomass. Low concentration of alcohols and low temperatures can improve bio-oil yields. Abstract: Although the hydrothermal liquefaction is considered a promising technology for converting microalgae into liquid biofuels, there are still some disadvantages. This paper demonstrated that the bio-oil yield can be significantly improved by adding alcohols as co-solvents and carrying out the conversion at mild conditions (<250 °C), but at the expense of a reduced bio-oil quality. By adding ethanol, the bio-oil yields obtained (up to ∼60%) were comparable to the yield obtained at severe operating conditions using only water as solvent (54 ± 2% on average), but the quality of the bio-oil was lower. However, the main advantages of the process here described lie in the utilisation of wet microalgae (∼75% moisture) and alcohol concentrations which avoid both drying the microalgae and decreasing the amount of microalgae loaded in the reactor.